2015
DOI: 10.14202/vetworld.2015.572-579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tanniferous leaf meal based multi-nutrient blocks on feed intake, hematological profile, immune response, and body weight changes in Haemonchus contortus infected goats

Abstract: Aim:The aim was to assess the effect of multi nutrient block (MNB) supplementation with and without tanniferous leaf meal mixture on feed intake, hematological profile, immune response, and body weight changes of goats that were experimentally infected with Haemonchus contortus.Materials and Methods:Total 12 adult male goats of similar age and body weight (26.49±0.87) were allocated in 3 groups in completely randomized design. MNB supplemented in first two groups i.e. in T1 (no infection) and T2 (H. contortus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
5
7
0
Order By: Relevance
“…In the present study, the lower level of ME and RIVIGP parameters is closely related to its CP, fiber fractions, and tannins as reported by previous studies [ 24 , 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the lower level of ME and RIVIGP parameters is closely related to its CP, fiber fractions, and tannins as reported by previous studies [ 24 , 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…The literature on the polyphenolic content of tree leaves depicts that the concentration remarkably varies from source to source. The polyphenolic content estimated was lower [ 17 , 24 , 25 ] than the present values, whereas a similar range of values was also observed in the past [ 15 , 16 , 26 - 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…Singh et al . [21] found that Hb and PCV levels were found to be highest (p<0.05) in treated group; however, the PCV values were found to be statistically non-significant in goats fed on multinutrient block supplementation with and without tanniferous leaf meal mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Max [30] revealed that dietary inclusion of quebracho extract as source of tannin appreciably reduced fecal egg counts in H. contortus infected sheep and goats. Supplementation of CT could be used as an alternative sustainable method to control H. contortus and maintained health status and performance of goats in the face of parasitic challenge [9,21]. The use of phytochemicals (CT) is becoming preferable and may offer better control than anthelmintics to treat GINs.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts are insoluble in this solvent thus only a limited number of scientists used this test for evaluation of efficacy. However, some workers modified LPT and have used acetone, ethanol and methanol in place of trichloroethylene (de Monteiro et al, 2012;Singh et al, 2015). Only condition of the solvent is that it should not cause mortality of tick's larvae more than 5% in control group.…”
Section: Plants Used As Acaricidesmentioning
confidence: 99%